Alternative Financing Model of Micro Small Medium Business (UMKM) Based on Productive Zakat by Amil Zakat Institution (LAZ) in Surabaya - Maulana, Alfin; Rijal, Akmalur; Arifin, Sirajul (Nursyam Center, 2023)
This article discusses the problems that arise in micro, small, and medium enterprises (UMKM) in Indonesia in general, namely capital problems, income distribution, and the quality of the products offered. Which of these problems can reduce the productivity of UMKM and ultimately cannot guarantee the welfare of the local community. The research method used is a qualitative descriptive approach. The author looks at the existing problems and proposes solutions by optimizing the means of productive zakat funds that have been collected by the Amil Zakat Institute (LAZ). The distribution of productive zakat funds as a source of funding is the main instrument in this article. The financing and development of UMKM by the Amil Zakat Institution (LAZ) is a solution to the problems of UMKM that have been going on for so long. As the Amil Zakat Institution, LAZ will provide business capital from productive zakat funds, foster entrepreneurship, and human resources, as well as aid and control UMKM actors who have received capital from the Amil Zakat Institution (LAZ). The pattern for developing UMKM is through productive zakat funds that have been collected by the Amil Zakat Institution (LAZ) for UMKM. The author will describe the mechanism and role of the Amil Zakat Institution (LAZ) in distributing productive zakat funds so that through this they can overcome the problems of UMKM. Based on this thought, the output expected by the author is to improve product quality, good distribution, and prosperity for UMKM and ultimately be able to create better economic conditions for the community.